Mortality in Iranian Patients with Parkinson's Disease: Cumulative Impact of Cardiovascular Comorbidities as One Major Risk Factor. (20th October 2015) - Fereshtehnejad, Seyed-Mohammad; Shafieesabet, Azadeh; Shafieesabet, Mahdiyeh; Shahidi, Gholam Ali; Delbari, Ahmad; Lökk, Johan
Abstract : Mortality rate, life expectancy, survival, and the impact of comorbidities on them in people with Parkinson's disease (PD) need to be assessed in settings with different sociodemographic backgrounds. We investigated mortality features in Iranian PD patients focusing on the role of cardiovascular multimorbidity on their survival. Data on mortality and comorbidity profile was gathered in a cohort of 190 individuals with idiopathic PD referred to a Movement Disorders Clinic. Standardized mortality ratio (SMR) compared to the Tehran general population was 3.44 and the life expectancy at birth was 67.4 (95% CI: 59.1–75.8) yr. Patients with at least one cardiovascular comorbidity had a shorter survival time after PD onset (14.0 versus 29.2 yr, p = 0.012 ). The hazard ratio for death increased 2.8 times (95% CI: 1.5–5.2, p = 0.002 ) with one additional cardiovascular comorbidity. Among all comorbid conditions, stroke showed the strongest independent effect on mortality in PD patients [HR = 13.1 (95% CI: 2.4–71.7), p = 0.003 ]. Conclusively, life expectancy was slightly lower in Iranian PD patients compared to the general population, while the SMR was high. Cardiometabolic multimorbidity substantially decreased survival in people with PD. Our study highlights the need for assessment, prevention, and treatment of cardiovascular morbidities in parkinsonian patients, given their effect on survival.